Pengaruh Orientasi Kewirausahaan terhadap produktivitas UMKM di Makassar - Ela Elliyana; Ambo Paerah; Syahribulan Syahribulan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
This study aims to examine the effect of entrepreneurial orientation on the marketing performance of MSMEs in the furniture industry in the city of Makassar. MSME players, especially the furniture industry, are growing rapidly and innovatively, so that the market demands them to have the ability to compete in marketing their products. A quantitative approach is used in this study. The research method uses the associative method, which aims to explain the causal relationship or cause and effect and the influence between variables through hypothesis testing. The research population is the owner of the furniture industry in Makassar. By using saturated sampling method in distributing questionnaires. The data analysis tool used is SPSS. The conclusion of the study shows that entrepreneurial orientation has a positive and significant effect on marketing performance. Furniture industry business owners continue to innovate, be proactive and dare to take risks as a competitive effort in winning the market.